INTEGRATED SYSTEM FOR AUTOMATED DESIGN AND MODELING OF PHYSICAL PROCESSES IN CONVECTIVE DRYING CHAMBERS USING SOLIDWORKS - RUBINSKYY, YURIY; KROSHNYY, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents an integrated system for automated design and modeling of physical processes in convective drying chambers using SolidWorks. The relevance of the study is due to the high complexity and labor intensity of manually creating three-dimensional models of drying chambers and wood stacks, which significantly slows down the engineering design process and complicates further analysis of heat and mass transfer. The proposed system provides end-to-end automation, covering the stages from setting the initial parameters of the wood and the geometry of the stack to building a finished three-dimensional model of the drying chamber and performing calculations in the SolidWorks Simulation environment. The developed software was created in C# using Windows Forms, which made it possible to implement a convenient graphical user interface for entering material parameters, board dimensions, number of rows, and characteristics of the chamber itself. Based on the entered data, SolidWorks macros are automatically generated, which build accurate 3D models of stacks and integrate them into the pre-formed drying chamber environment. This significantly reduces design time and minimizes errors that occur during manual modeling. The chamber model includes an axial fan with water heating, which ensures uniform air flow distribution and stable temperature conditions. The use of SolidWorks Simulation in combination with automatically generated three-dimensional models makes it possible to perform detailed studies of the thermal and hydrodynamic characteristics of the drying process. This paves the way for a more accurate analysis of the uniformity of stack heating, the identification of critical areas with uneven energy distribution, and the evaluation of the effectiveness of design solutions. Therefore, the proposed system combines design and computer modeling tools, creating a universal basis for improving the accuracy, speed, and reliability of engineering developments in the field of wood drying.